Kajian Literatur tentang Penggunaan Media GeoGebra dalam Pembelajaran Fungsi Kuadrat di Sekolah Menengah Atas - Tabitha Gabriela Sianipar; Nurhasanah Siregar (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Learning quadratic functions in high school still faces various challenges, primarily due to the abstract nature of the concepts, which require students to have strong analytical thinking skills. These difficulties often result in low student understanding of the relationship between quadratic equations and parabola graphs, as well as limitations in applying these concepts to mathematical problem-solving. GeoGebra, as a technology-based learning tool, offers interactive visualizations that allow students to observe the real-time changes in the shape of a parabola when the coefficients in a quadratic equation are modified. A literature review of recent studies reveals that the use of GeoGebra significantly enhances conceptual understanding, mathematical representation skills, and student motivation. Its effectiveness further increases when combined with appropriate teaching strategies, such as the 5E model (Engage, Explore, Explain, Elaborate, Evaluate), which encourages active involvement and concept exploration by students. However, several challenges remain, including limited access to devices, teachers’ readiness to utilize technology, and suboptimal infrastructure support. Therefore, the integration of GeoGebra into quadratic function learning requires careful planning, teacher training, and adequate facility support to maximize its benefits and improve the overall quality of mathematics education.